Evaluasi Instalasi Kelistrikan Pada Gedung Vessel Traffic Service Palembang - Merry Dhani Anitasari; M. Saleh Al Amin; Irine Kartika F; Yudi Irwansi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Electrical installation is one of the important elements in buildings. Safe electrical installations that comply with applicable safety standards can prevent electrical accidents. This research aims to evaluate the electrical installation in the Palembang Vessel Traffic Service (VTS) Building. Evaluation is carried out by measuring and calculating several parameters, namely: voltage and current values, current carrying capacity (KHA), circuit breaker (CB) size, short circuit impedance, grounding value. Quantitative research methods were used because this research aims to evaluate the electrical installation at the Palembang Vessel Traffic Service (VTS) Building. Evaluation is carried out by comparing the results of measurements and calculations with applicable standards. Based on the research results, it can be concluded that the electrical installations of the Palembang VTS Building generally meet safety requirements and comply with applicable standards. However, there are several recommendations that can be made to increase the safety of electrical installations, namely: The results of checking that the electrical current on the 7th and 8th floors is unbalanced must immediately identify the cause and repair the load group points so that the electrical load is evenly distributed so that power losses do not occur and result in damage to the existing electrical installation.